3-(18)F-Fluoropropane-1-thiol and (18)F-PEG(4)-1-thiol: versatile prosthetic groups for radiolabeling maleimide functionalized peptides - Jacobson, Orit (Bioorg Med Chem, 2019)
The efficient radiosynthesis of biomolecules utilizing minute quantities of maleimide substrate is important for availability of novel peptide molecular imaging agents. We evaluated both 3-(18)F-fluoropropane-1-thiol and 2-(2-(2-(2-(18)F-fluoroethoxy)ethoxy)ethoxy)ethane-1-thiol ((18)F-fluoro-PEG(4) thiol) as prosthetic groups for radiolabeling under physiological conditions. The precursor employed a benzoate for protection of the thiol and an arylsulfonate leaving group. The radiofluorination was fully automated on an Eckert & Ziegler synthesis system using standard Kryptofix(222)/K(2)CO(3) conditions. In order to minimize the amount of biological molecule required for subsequent conjugation, the intermediates, S-(3-(18)F-fluoropropyl) benzothioate and (18)F-fluoro-PEG(4) benzothioate, were purified by HPLC. The intermediates were isolated from the HPLC in yields of 37 – 47% and 28 – 35%, respectively, and retrieved from eluate using solid phase extraction. Treatment of the benzothioates with sodium methoxide followed by acetic acid provided the free thiols. The desired maleimide substrate in acetonitrile or phosphate buffer was then added and incubated at room temperature for 15 min. The final radiolabeled bioconjugate was purified on a separate HPLC or NAP-5 column. Maleimides utilized for the coupling reaction included phenyl maleimide, an Evans Blue maleimide derivative, a dimeric RGDfK maleimide (E[c(RGDfK)](2)), two aptamer maleimides, and PSMA maleimide derivative. Isolated radiochemical yields (non-decay corrected) of maleimide addition products based on starting (18)F-fluoride ranged from 6 – 22 % in a synthesis time of about 90 min. (18)F-thiol prosthetic groups were further tested in vivo by conjugation to E[c(RGDfK)](2) maleimide in a U87MG xenograft model. PET studies demonstrated similar tumor accumulation of both prosthetic groups. (18)F-fluoro-PEG(4)-S-E[c(RGDfK)]2 displayed a somewhat favorable pharmacokinetics compared to (18)F-fluoropropyl-S-E[c(RGDfK)](2). Bone uptake was low for both indicating in vivo stability.